2020
DOI: 10.1108/rausp-05-2019-0113
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory dividend and corporate investment: a multi-country analysis

Abstract: Purpose This paper aims to empirically verify the impact of the mandatory dividend law on the investment of publicly traded companies. Design/methodology/approach The sample includes 212,595 observations from publicly traded companies from 47 different countries over the period from 2000 to 2016. The authors estimated a regression model by panel data methods to show the impact of the mandatory dividend on firm’s investment, more specifically in their sensitivities of investment to cash flow and to growth opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The ATE method is a commonly used technique to estimate the effect of a policy/regulation change on firms’ actions across different domains, e.g. Li et al (2020), Vancin and Kirch (2020); and Iselin (2020). Ioannou and Serafeim (2017) use ATE to explore the impact of sustainability disclosure regulations on regulated firms’ ESG disclosures in China, Denmark, Malaysia and South Africa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ATE method is a commonly used technique to estimate the effect of a policy/regulation change on firms’ actions across different domains, e.g. Li et al (2020), Vancin and Kirch (2020); and Iselin (2020). Ioannou and Serafeim (2017) use ATE to explore the impact of sustainability disclosure regulations on regulated firms’ ESG disclosures in China, Denmark, Malaysia and South Africa.…”
Section: Methodsmentioning
confidence: 99%
“…Significantly positive values of b 1 indicate the effectiveness of the EU directive in increasing the ESG disclosures of the treated firms. The ATE method is a commonly used technique to estimate the effect of a policy/regulation change on firms' actions across different domains, e.g Li et al (2020),Vancin and Kirch (2020);and Iselin (2020)Ioannou and Serafeim (2017).…”
mentioning
confidence: 99%
“…The impact of internal factors on innovation focuses mainly on compensation and incentive policies, the characteristics of senior management teams, media reports, investment behaviors, equity structures, and property rights. Vancin and Kirch [27] and Saens and Tigero [9] found that if companies implement mandatory dividend policies, then they can help increase investment opportunities but will exacerbate the financing constraints caused by innovative investments. Corporate compensation incentives are not only for management but also nonexecutive employee equity incentives, which can help alleviate agency issues to motivate employees to increase their risk tolerance and actively participate in corporate innovation [10,28].…”
Section: Influencing Factors Of Enterprise Innovationmentioning
confidence: 99%